CONSORT 2010 Statement: updated guidelines for reporting parallel group randomised trials - Schulz, Kenneth F (BMJ Publishing Group Ltd., 2010)
The CONSORT statement is used worldwide to improve the reporting of randomised controlled trials. Kenneth Schulz and colleagues describe the latest version, CONSORT 2010, which updates the reporting guideline based on new methodological evidence and accumulating experience